Yūsuf Zulaiḵẖā : shuhrah-yi āfāq Sirāʼekī mas̲navī kā salīs Urdū tarjamah maʻ matn - ʻAbdulḥakīm Ūcī (Urdū Akaiḍmī, 1978)
A classical narrative poem, describing the story of Prophet Joseph, based on the Koran.